Be creative making a living in the new culture industries - McRobbie, Angela (Cambridge, United Kingdom Polity Press, 2016)
"In this exciting new book Angela McRobbie charts the 'euphoric' moment of the new creative economy, as it rose to prominence in the UK during the Blair years, and considers it from the perspective of contemporary experience of economic austerity and uncertainty about work and employment. McRobbie makes some bold arguments about the staging of creative economy as a mode of 'labour reform'; she proposes that the dispositif of creativity is a fine-tuned instrument for acclimatising the expanded, youthful urban middle classes to a future of work without the raft of entitlements and security which previous generations had struggled to win through the post-war period of social democratic government. Adopting a cultural studies perspective, McRobbie re-considers resistance as 'line of flight' and shows what is at stake in the new politics of culture and creativity. She incisively analyses 'project working' as the embodiment of the future of work and poses the question as to how people who come together on this basis can envisage developing stronger and more protective organisations and associations. Scattered throughout the book are excerpts from interviews with artists, stylists, fashion designers, policy-makers, and social entrepreneurs"-- Provided by publisher.
Introduction : From the social network to the 'flexible frau', visions of creative economy -- Chapter one: Unpacking the politics of creative labour : the rise of the urban hipster economy -- Chapter two: The artist as human capital: looking back at London, new labour and the 'modernisation of culture' -- Chapter three: Club to company -- Chapter four: Gender and work in the new creative economy -- Chapter five: The time and space of creative labour: a response to the writing of Richard Sennett -- Chapter six: Fashion matters Berlin: start ups scenes and female social enterprise -- Chapter seven: conclusion; concepts for project working in a European frame.
Keywords: Cultural industries; Cultural industries -- Employees; Arts -- Economic aspects